Grey-to-white matter ratio on computed tomography for predicting neurological outcome in patients with heat stroke: a retrospective cohort study - Wei, Hua; Zhu, Hongling; Liu, Menglong; Zhu, Xiaodan; Yu, Anyong; Luo, Can; Zeng, Qingbo; Zhou, Fating; Duan, Haizhen (Frontiers in Neurology, 2025)
ObjectiveGrey-to-white matter ratio (GWR) is an early and sensitive indicator of cerebral oedema in patients with hypoxic-ischaemic brain injury, we aimed to evaluate the prognostic value of GWR for predicting neurological outcome in heat stroke patients.MethodsThis multicentre retrospective analysis included 86 patients with heat stroke patients who underwent cranial computed tomography (CT). Patients were stratified by Cerebral Performance Category (CPC) scores at discharge: good outcome (CPC 1–2, n = 65) versus poor outcome (CPC 3–5, n = 21) in the derivation cohort. Seven GWR parameters were calculated from Hounsfield unit measurements at three different regions (basal ganglia, centrum semiovale, high convexity): putamen/corpus callosum (PU/CC), caudate nucleus/posterior limb of internal capsule (CN/PLIC), CN/CC, PU/PLIC, GWRbasal ganglia, GWRcerebrum, and GWRaverage. Prognostic performance of GWR was compared with qSOFA using receiver operating characteristic (ROC) analysis. And a validation cohort was used to verify the reliability.ResultsAll GWRs were significantly lower in the poor outcome group than in the good outcome group. ROC analysis showed the following areas under the curve: PU/CC, 0.836; CN/PLIC, 0.815; CN/CC, 0.858; PU/PLIC, 0.814; GWRbasal ganglia, 0.855; GWRcerebrum, 0.803; GWRaverage, 0.837. The cutoff values with 90.77% specificity in predicting poor outcome were as follows: PU/CC, 1.20 (sensitivity, 76.19%); CN/PLIC, 1.17 (sensitivity, 52.38%); CN/CC, 1.20 (sensitivity, 76.19%); PU/PLIC, 1.20 (sensitivity, 61.90%); GWRbasal ganglia, 1.23 (sensitivity, 80.95%); GWRcerebrum, 1.19 (sensitivity, 57.14%); GWRaverage, 1.23 (sensitivity, 71.43%). The sensitivity of GWRbasal ganglia significantly increased when combined with qSOFA in the derivation and validation cohorts.DiscussionA low GWR was strongly associated with poor outcome in the heat stroke patients. The GWR may be useful as an objective early predictor of poor neurological outcome in the heat stroke patients. Incorporating the GWR with qSOFA significantly enhanced the prediction performance.